Potensi Imunomodulator Alami Ekstrak Daun Kelor (Moringa oleifera Lam.) dan Daun Salam (Eugenia polyantha Wight) dalam Meningkatkan Sistem Imunitas Tubuh - W.O. Mulyana; M. Agustinus W.; Fatahu Fatahu; A.L. Nugrawati M.; Y. Tewa (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Research on the natural immunomodulatory potential of Moringa leaf extract (Moringa oleifera lam.) And Salam leaf (eugenia polyantha wight) in enhancing the immune system has been carried out. This study aims to determine the antioxidant activity that has the potential as a natural immunomodulator that can increase the body's immune system. Stages in this study is the extraction of the sample leaf maceration using ethanol for 3 x 24 hours and then extract the results of maceration concentrated by rotary evaporator. Testing of sample extracts includes phytochemical tests to determine the secondary methobite content contained in the sample extract and antioxidant activity testing using the DPPH free radical inhibition method. Results of phytochemical analysis showed extracts of moringa leaves and salam leaves contain alkaloids, flavonoids, saponins, polyphenols and tannins are strong.Meanwhile, the steroid and triterpenoid tests showed the opposite result. The results of the analysis of the antioxidant activity as measured by IC50 value indicates that the optimal inhibitory concentration of ethanol extract of moringa leaves, salam leaves and extracts a combination of both, respectively, are 95.08 ppm, 41.71 ppm and 43.67 ppm. As for vitamin C as comparison had IC50 value of 52.16 ppm. The relationship between antioxidant activity and the immune system (body immunity) is seen in maintaining the balance and availability of antioxidant compounds present in the body in protecting the body from guilty foreign substances from outside the body